Functionalization of gold nanorods with antimicrobial peptides - Asaad, Mohamed (My University, 2023)
Infections in biomedical implants can occur due to the growth of bacterial biofilms, and treating these infections becomes even more challenging due to problems such as antimicrobial resistance. Gold nanorods (NRs) provide an alternative approach to combating bacterial infections. When exposed to radiation, gold nanorods generate heat, which can be employed to eliminate bacteria. Antimicrobial peptides (AMPs) are naturally occurring peptides known for their potent ability to kill microorganisms. A combination between gold nanorods and AMPs could potentially show promising results and open up for new, safe and efficient treatment options of bacteria. The primary objective of this study was to investigate the interaction between gold nanorods and antimicrobial peptides, focusing on optimizing the attachment of these peptides to the nanorods. Two distinct types of antimicrobial peptides were employed: one with a positive charge and another one terminated with thiol groups. In the case of the positively charged antimicrobial peptide, it was observed that the removal of CTAB from the gold nanorods resulted in increased peptide attachment to the nanorods. Interestingly, it was also noted that the peptide not only bonded through thiol groups but also exhibited unfavorable attachment to the surface onto which the gold nanorods were coated, likely due to electrostatic interactions. To address this issue, two different strategies were applied. The first involved adjusting the pH of the system to induce electrostatic repulsion, while the second utilized a PEG silane polymer to block peptide attachment to the surface. Both approaches effectively reduced the amount of peptide binding to the surface. Additionally, introducing a pH of 11.5 with NaOH as the initial step in the QCMD measurement resulted in a cleaner silica surface, enhancing the attachment of various components. For the thiol-terminated antimicrobial peptides, UV-Vis analysis revealed that these peptides exclusively attached to the surface through thiol bonding. Notably, A fascinating revelation came to light when exploring the temperature at which these peptides detached from the gold nanorods. Beyond 45°C, an additional resonance peak emerged at approximately 970 nm, adding an interesting dimension to the findings.
Keywords: gold nanorods; antimicrobial peptides; QCMD; thiol boding; resonance peak